1999
DOI: 10.1177/109980049900100107
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Aerobic Fitness on the Physiological Stress Response in Women

Abstract: Stress reactivity was assessed in aerobically fit (n = 14) and unfit (n = 8) females during the follicular phase of the menstrual cycle. Participants completed the Spielberger State-Trait Anxiety Inventory and provided a urine sample for catecholamine analysis before and after mental stress testing, Stroop Color-Word Test. Blood pressure, heart rate, muscle tension, and skin conductance were measured during mental stress testing. Fit and unfit participants differed significantly in baseline heart rate but not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

5
7
0

Year Published

2002
2002
2015
2015

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 27 publications
5
7
0
Order By: Relevance
“…Summers and colleagues reported no differences in urinary catecholamine responses to psychological stress in fit and unfit women [14]. This is in line with the comparable changes in Adr and NA observed in the current study in low-fit and high-fit women.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Summers and colleagues reported no differences in urinary catecholamine responses to psychological stress in fit and unfit women [14]. This is in line with the comparable changes in Adr and NA observed in the current study in low-fit and high-fit women.…”
Section: Discussionsupporting
confidence: 94%
“…Women are underrepresented in investigations regarding fitness and stress responsiveness [13], and the limited research undertaken in women has been inconclusive. Summers and colleagues reported no differences in urine catecholamines in response to a Stroop color-word task in fit versus unfit women [14]. Nevertheless, only two samples of urine (immediately before and after stress induction) were collected in this study.…”
Section: Introductionmentioning
confidence: 96%
“…After the training period (12 weeks) subjects underwent a mental stress paradigm: in comparison to the strength group the aerobic group showed a significantly reduced cardiovascular response (heart rate, diastolic blood pressure) and a trend towards lower epinephrine secretion. In contrast, mental stress testing (Stroop colour word test) did not lead to different physiological responses (blood pressure, heart rate, muscle tension, and skin conductance), when 14 fit and and 8 unfit women were compared [38], Accordingly, the present study did not reveal any differences between trained and untrained subjects during and after a slightly modified version of the Trier psychosocial stress test. The lack of differences cannot be explained by the assumption that the fitness level of the 2 groups might not have been different enough: data from the bicycle spiroergometry demonstrate that this sample of marathon runners in fact represented a very high fitness group.…”
Section: Discussionmentioning
confidence: 62%
“…Sinyor and colleagues (1983) were able to demonstrate that aerobically trained persons were able to recover faster from experimentally induced psychosocial stress than untrained persons on physiological, biochemical and psychological measures. Various similar physiologicallyorientated studies have demonstrated similar effects (Anshel, 1996;Scully, 1998;Summers, 1999). Related studies by Holmes (1985, 1987) have indicated that physical fitness moderates the stress-illness relationship and that increasing fitness, through aerobic training, decreases the experience of stressful life events.…”
mentioning
confidence: 85%